Cardiotoxic effects of chemotherapeutical treatment in oncological patient - D. P. Kotova; V. S. Shemenkova; N. N. Semenov; A. A. Udovichenko; A. A. Bogdanova (Klinicist)
The aim of study was to describe the clinical case of possible development of cardiac complications in patient after the chemotherapeutical treatment.Materials and methods. Patient Sh., 63 years old, admitted to N.I. Pirogov City Clinical Hospital № 1 of Moscow Healthcare Department in connection with new onset of anginalprecordialgia. In anamnesis: rectum adenocarcinoma with multiple courses of chemotherapy of first and second lines. The last course of chemotherapy was performed a month before the previous complaints. Previously, coronary anamnesis was not burdened.Results. During the examination, signs of ischemia on the electrocardiogram, diffuse hypokinesia of the left ventricular myocardium according to echocardiography, subocclusion of the anterior interventricular branch of the left coronary artery were identified. Balloon angioplasty and stenting of the anterior interventricular branch of the left coronary artery were performed with good perfusion effect.Conclusion. In this clinical case, ischemic complications in patient receiving chemotherapeutical treatment are displayed.